Laccaria fraterna (Cooke & Mass: : Sacc.) pegler, 1965 (agaricales, basidiomycota) associated with exotic eucalyptus sp. in northern Argentina and Paraguay - Campi Gaona, Michelle Geraldine (2017)
Fil: Campi Gaona, Michelle Geraldine. Universidad Nacional de Asunción. Facultad de Ciencias Exactas y Naturales; Paraguay.